The effect of sodium lauryl sulphate on blue stain, mould growth and surface properties of SA pine - Perold, Maurits (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2006.